Evaluation of the immunological functions of placental alkaline phosphatase in vivo using ALPP transgenic mice - Chen, Tse-Ching; Ng, Kwai-Fong; Chen, Ning; Pan, Yi-Ling; Cheng, Chun-An; Wu, Hsiao-Chun; Hsueh, Yi-Jen; Chiang, Nien-Yi; Lin, Hsi-Hsien (Frontiers in Immunology, 2025)
Alkaline phosphatase (ALP) is a ubiquitously expressed dephosphorylating enzyme and its level in blood is widely used as a diagnosis marker of liver damage or bone disorders in human patients. ALP is also considered as an anti-inflammatory protein due to its ability to dephosphorylate and inactivate inflammation-triggering molecules such as lipopolysaccharide (LPS). Placental alkaline phosphatase (ALPP) is one of tissue-specific ALP isozymes expressed mostly during pregnancy, however it was found to be differentially upregulated in certain hepatocellular carcinomas by us recently. In addition, ALPP has been identified as a reliable biomarker of diverse germ cell tumors. Nevertheless, little is known of its immune modulatory role in vivo. In this study, we generated ALPP transgenic mice and tested these mice in the LPS-induced sepsis and male-to-female skin graft rejection models. Our results showed that ALPP transgenic mice are more susceptible to intraperitoneal injection of LPS in comparison to control animals. In addition, female ALPP transgenic mice were better at delaying the rejection of male skin grafts. In an in vitro phagocytosis experiment, addition of exogenous ALPP compromised the phagocytic ability of THP-1 monocytic cells. These results indicate that excess ALPP plays a role in modulating both innate and adaptive immune functions.